2012
DOI: 10.7182/pit2012241
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab for Cytolytic Induction of Immunosuppression in Heart Transplant Recipients

Abstract: Although alemtuzumab may be a practical option for inducing immunosuppression, data are insufficient to recommend its routine use in deference to more established agents. Large, randomized clinical trials with extended durations of follow-up must be conducted to characterize its efficacy and safety further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…These initial results were then confirmed in a larger case control series by Teuteberg et al [43][44][45][46][47]. Further studies on alemtuzumab are, however, needed before its routine use can be considered [48].…”
Section: Anti-cd52 Antibodiessupporting
confidence: 53%
“…These initial results were then confirmed in a larger case control series by Teuteberg et al [43][44][45][46][47]. Further studies on alemtuzumab are, however, needed before its routine use can be considered [48].…”
Section: Anti-cd52 Antibodiessupporting
confidence: 53%
“…In our analysis of the UNOS/STAR database, we found that the use of antibody based induction immunosuppression in heart transplant recipients, in general, is not associated with significant differences in overall survival. Previously published reports have demonstrated an accepted improvement in general outcomes with antibody based induction therapy .…”
Section: Discussionmentioning
confidence: 94%
“…In our analysis of the UNOS/STAR database, we found that the use of antibody based induction immunosuppression in heart transplant recipients, in general, is not associated with significant differences in overall survival. Previously published reports have demonstrated an accepted improvement in general outcomes with antibody based induction therapy (5)(6)(7)(8)(9)(10)(11)(12). The agents used in these reports have been variedranging from the IL-2 receptor antibodies (basiliximab or daclizumab), T-cell depleting agents (anti-thymocyte globulin [ATG], anti-lymphocyte globulin [ALG], and thymoglobulin), CD52 monoclonal antibody (alemtuzumab), to monoclonal anti-CD3 agent OKT3.…”
Section: Discussionmentioning
confidence: 99%
“…Alemtuzumab, a monoclonal antibody that binds to CD52, can result in destruction of complement-mediated peripheral immune cells (monocytes, lymphocytes, macrophages, natural killer cells, and dendritic cells). Although the use of alemtuzumab in the context of cardiac allograft rejection has previously been evaluated, data on its use in patients with irAEs is limited (Cahoon et al, 2012). A recent report has indicated that 30 mg of alemtuzumab led to rapid T-cell depletion and was associated with the resolution of cardiac immunotoxic effects (Esfahani et al, 2019).…”
Section: Treatment and Outcome Of Immune Checkpoint Inhibitor-associamentioning
confidence: 99%